Quantifying metal emissions from vehicular traffic using real world emission factors. (1st January 2021) - Wang, Jonathan M.; Jeong, Cheol-Heon; Hilker, Nathan; Healy, Robert M.; Sofowote, Uwayemi; Debosz, Jerzy; Su, Yushan; Munoz, Anthony; Evans, Greg J.
Abstract: Road traffic emissions are an increasingly important source of particulate matter in urban and non-road environments, where non-tailpipe emissions can contribute substantially to elevated levels of metals associated with adverse health effects. Thus, better characterization and quantification of traffic-emitted metals is warranted. In this study, real-world emission factors for fine particulate metals were determined from hourly x-ray fluorescence measurements over a three-year period (2015–2018) at an urban roadway and busy highway. Inter-site differences and temporal trends in real-world emission factors for metals were explored. The emission factors at both sites were within the range of past studies, and it was found that Ti, Fe, Cu, and Ba emissions were 2.2–3.0 times higher at the highway site, consistent with the higher proportion of heavy-duty vehicles. Weekday emission factors for some metals were also higher by 2.0–3.5 times relative to Sundays for Mn, Zn, Ca, and Fe, illustrating a dependence on fleet composition and roadway activity. Metal emission factors were also inversely related to relative humidity and precipitation, due to reduced road dust resuspension under wetter conditions. Correlation analysis revealed groups of metals that were co-emitted by different traffic activities and sources. Determining emission factors enabled the isolation of traffic-related metal emissions and also revealed that human exposure to metals in ambient air can vary substantially both temporally and spatially depending on fleet composition and traffic volume. Graphical abstract: Image 1 Highlights: Emission factors determined for trace metals from continuous hourly measurements at two near road sites. Ti, Fe, Cu, and Ba emissions were ∼2.2–3.0 times higher by the highway due to more heavy-duty vehicle brake wear and volume. Mn, Zn, Ca, and Fe emissions were ∼2.0–3.5 times higher on weekdays vs. Sundays due to differences in fleet composition. Correlation analysis of emission factors revealed groups of metals that were likely co-emitted.